2018
DOI: 10.1007/s40279-018-0926-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Dose–Response Relationship of Balance Training on Balance Performance in Youth: A Systematic Review and Meta-Analysis

Abstract: BT is a highly effective means to improve balance performance with moderate to large effects on static and dynamic balance in healthy youth irrespective of age, sex, training status, setting and testing method. The examined training modalities did not have a moderating effect on balance performance in healthy adolescents. Thus, we conclude that an additional but so far unidentified training modality may have a major effect on balance performance that was not assessed in our analysis. Training intensity could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 58 publications
3
61
0
2
Order By: Relevance
“…As balance performance in children is limited due to their still maturing postural control system and poor balance is associated with an increased risk of falling and sustaining an injury, previous research has focused on balance trainability of children. A systematic review with meta-analysis [27] did not find sex to have a significant influence on balance trainability. However, the researchers emphasized the preliminary character of their findings as they observed a lack of high quality studies on this topic.…”
Section: Discussionmentioning
confidence: 95%
“…As balance performance in children is limited due to their still maturing postural control system and poor balance is associated with an increased risk of falling and sustaining an injury, previous research has focused on balance trainability of children. A systematic review with meta-analysis [27] did not find sex to have a significant influence on balance trainability. However, the researchers emphasized the preliminary character of their findings as they observed a lack of high quality studies on this topic.…”
Section: Discussionmentioning
confidence: 95%
“…There is ample evidence on the general effectiveness of balance training on balance performance in youth as indicated in randomized controlled trials ( Granacher et al, 2010a ; Pau et al, 2012 ; Donath et al, 2013 ) and recent systematic reviews ( Gebel et al, 2018 ). In an attempt to extend the findings of Granacher et al (2010a) who demonstrated that balance training is suitable to enhance ST postural control, specifically designed intervention programs during PE may have the potential to improve postural control not only in ST but also in DT situations.…”
Section: Introductionmentioning
confidence: 99%
“…Postural stability is associated with inertial forces acting on the body and inertial characteristics of body segments. Therefore, postural stability is determined by body composition and structure [20,21]. In the literature, it is difficult to find similar studies in which body composition would be assessed with Tanita electrical bioimpedance and postural stability with Ac-cuGait AMTI.…”
Section: Discussionmentioning
confidence: 99%